Biomonitoring of perfluoroalkyl and polyfluoroalkyl substances (PFAS) from the Survey of the Health of Wisconsin (SHOW) 2014-2016 and comparison with the National Health and Nutrition Examination Survey (NHANES) - Schultz, Amy A; Stanton, Noel; Shelton, Brandon; Pomazal, Rachel; Lange, Meshel A; Irving, Roy; Meiman, Jonathan; Malecki, Kristen C (Journal of exposure science & environmental epidemiology, 2023)
Per- and polyfluoroalkyl substances (PFAS) are a growing class of manufactured chemical compounds found in a variety of consumer products. PFAS are ubiquitous in the environment and were found in many humans sampled in the United States (U.S.). Yet, significant gaps in understanding statewide levels of exposure to PFAS remain. The goals of this study are to establish a baseline of exposure at the state level by measuring PFAS serum levels among a representative sample of Wisconsin residents and compare to United States National Health and Nutrition Examination Survey (NHANES). The study sample included 605 adults (18+ years of age) selected from the 2014-2016 sample of the Survey of the Health of Wisconsin (SHOW). Thirty-eight PFAS serum concentrations were measured using high-pressure liquid chromatography coupled with tandem mass spectrometric detection (HPLC-MS/MS) and geometric means were presented. Weighted geometric mean serum values of eight PFAS analytes from SHOW were compared to U.S. national levels from the NHANES 2015-2016 sample (PFOS, PFOA, PFNA, PFHxS, PFHpS, PFDA, PFUnDA), and the 2017-2018 sample for Me-PFOSA, PFHPS using the Wilcoxon rank-sum test. PFOS, PFHxS, PFHpS, PFDA, PFNA, and PFOA were detected in over 96% of SHOW participants. In general, SHOW participants had lower serum levels across all PFAS when compared to NHANES. Serum levels increased with age and were higher among males and whites. Similar trends were seen in NHANES, except non-whites had higher PFAS levels at higher percentiles in NHANES. The present study conducts biomonitoring of 38 PFAS among representative sample of residents in the state of Wisconsin. Results suggest that while the majority of Wisconsin residents tested have detectable levels of PFAS in their blood serum, they may have a lower body burden of some PFAS compared to a nationally representative sample. Older adults, males, and whites may have a higher body burden of PFAS relative to other groups, both in Wisconsin and the wider United States.